Restoration potential of degraded inland sacred forest of Kachchh, Gujarat: An evidence of shravan kavadiya sacred grove - AMIT PANDEY; ARUN KUMAR ROY MAHATO (International Journal of Pharma and Bio Sciences, 2019)
Desert Ecosystems are harsh, less productive but are significant in terms of biological diversity because forest patches in desert systems play a keystone function. Indian deserts have not received the conservation attention in comparison to their counterparts as their global priorities have been low. Among the deserts, the Orans of Rajasthan are sacred groves revered and managed by the Bishnoi community possess a rich literature; however, the sacred groves of Kachchh region are revered because of cultural association is relatively less studied. Sacred groves provide ecosystem services through its inherent biodiversity, soil and moisture conservation, nutrient cycling, water regulation and carbon sequestration. These groves play a very important role in terms of conserving biological diversity and provide livelihood security of the local communities of arid India. The sparsely distributed sacred groves of this region face several stages of degradation by natural as well as of anthropogenic pressure. Restoration of such groves would require scientific strategy and conservation planning along with community participation. Thus, the aim of the present study is to evaluate the restoration potential of degraded sacred grove of Kachchh in comparison with the existing sacred grove of arid Kachchh by analyzing the major soil parameters of both groves.